2020
DOI: 10.1590/1516-3180.2019.0304.r2.09122019
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum levels of secreted frizzled-related protein 5 and Wnt member 5a with glomerular filtration rate in patients with type 2 diabetes mellitus and chronic renal disease: a cross-sectional study

Abstract: BACKGROUND: Diabetic nephropathy is a common complication of chronic kidney disease (CKD). Inflammation in the kidneys is crucial for promoting development and progression of this complication. Wnt member 5a (Wnt5a) and secreted frizzled-related protein 5 (Sfrp5) are proinflammatory proteins associated with insulin resistance and chronic low-grade adipose tissue inflammation. OBJECTIVE: To determine the correlation between serum Sfrp5 and Wnt5a concentrations and glomerular filtration rate in patients with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Recent studies suggest that metabolic inflammation may contribute to elevated serum SFRP5 levels, as several diseases with concomitant systemic inflammatory responses have significantly higher SFRP5 levels than the normal baseline [27,[51][52][53]. Similarly, excessive systemic inflammation is also an important feature of PE, which causes extensive damage to the vascular endothelium, leading to the appearance of clinical symptoms [1].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that metabolic inflammation may contribute to elevated serum SFRP5 levels, as several diseases with concomitant systemic inflammatory responses have significantly higher SFRP5 levels than the normal baseline [27,[51][52][53]. Similarly, excessive systemic inflammation is also an important feature of PE, which causes extensive damage to the vascular endothelium, leading to the appearance of clinical symptoms [1].…”
Section: Discussionmentioning
confidence: 99%
“… 91 Likewise, Wnt5a is highly expressed in ischaemic muscles and ECs from mice overexpressing glutaredoxin‐1, an oxidation‐promoting enzyme which is increased in T2DM patients, and exogenous Wnt5a treatment could inhibit the revascularization in hind limb ischaemia via activating the non‐canonical Wnt pathway, 92 indicating a deleterious role of Wnt5a in diabetic foot. Although the increase in serum concentration of Wnt5a and a negative correlation between serum Wnt5a and glomerular filtration rate are detected in patients with DP, 93 more studies tend to prove the protective role of Wnt5a in the development of DP. It has been shown that a weak Wnt5a expression is detected in glomerular mesangium of diabetic rat and glomerular cells cultured in high glucose condition.…”
Section: Roles Of Wnts In T2dm and Related Complicationsmentioning
confidence: 97%
“…However, the effects of non-classical WNT signaling were rarely reported. WNT5A, a typical glycoprotein of the noncanonical pathway, has been verified to have pro-inflammatory functions in urosepsis, nephrogenic diabetes insipidus (NDI), and chronic kidney disease (CKD) (28)(29)(30). WNT5A signaling play potential roles in human placental and malfunction of it can cause preeclampsia (31,32).…”
Section: Introductionmentioning
confidence: 99%